International Geographic Variation in Event Rates in Trials of Heart Failure With Preserved and Reduced Ejection Fraction. Issue 1 (6th January 2015) - Kristensen, Søren L.; Køber, Lars; Jhund, Pardeep S.; Solomon, Scott D.; Kjekshus, John; McKelvie, Robert S.; Zile, Michael R.; Granger, Christopher B.; Wikstrand, John; Komajda, Michel; Carson, Peter E.; Pfeffer, Marc A.; et al.
Abstract : Background—: International geographic differences in outcomes may exist for clinical trials of heart failure and reduced ejection fraction (HF-REF), but there are few data for those with preserved ejection fraction (HF-PEF). Methods and Results—: We analyzed outcomes by international geographic region in the Irbesartan in Heart Failure with Preserved systolic function trial (I-Preserve), the Candesartan in Heart failure Assessment of Reduction in Mortality and morbidity (CHARM)-Preserved trial, the CHARM-Alternative and CHARM–Added HF-REF trials, and the Controlled Rosuvastatin Multinational Trial in HF-REF (CORONA). Crude rates of heart failure hospitalization varied by geographic region, and more so for HF-PEF than for HF-REF. Rates in patients with HF-PEF were highest in the United States/Canada (HF hospitalization rate 7.6 per 100 patient-years in I-Preserve; 8.8 in CHARM-Preserved), intermediate in Western Europe (4.8/100 and 4.7/100), and lowest in Eastern Europe/Russia (3.3/100 and 2.8/100). The difference between the United States/Canada versus Eastern Europe/Russia persisted after adjustment for key prognostic variables: adjusted hazard ratios 1.34 (95% confidence interval, 1.01–1.74; P =0.04) in I-Preserve and 1.85 (95% confidence interval, 1.17–2.91; P =0.01) in CHARM-Preserved. In HF-REF, rates of HF hospitalization were slightly lower in Western Europe compared with other regions. For both HF-REF and HF-PEF, there were few regional differences in rates of all-cause or cardiovascular mortality. Conclusions—: The differences in event rates observed suggest there is international geographic variation in 1 or more of the definition and diagnosis of HF-PEF, the risk profile of patients enrolled, and the threshold for hospitalization, which has implications for the conduct of future global trials. Abstract : Supplemental Digital Content is available in the text.